A Comparative Analysis of Advance Toll Tax Systems (International Journal of Innovative Research in Computer Science & Technology, 2020)
Many vehicles drive on the highway, and toll  taxes must be collected as they pass by. However, this is a  time-consuming operation, and poor management may result  in long lines and pollution. By using Automation in Toll  Collection, several solutions have been created to decrease  the complexity of the operation. There are a number of  systems available; we examine a few of them and look for  areas where they might be improved. ATCSR is an RFID based Automated Toll Collection System that collects taxes  automatically. We use radio frequency to perform the  identification in this case. An RFID tag will be attached to a  car. This tag is just an exceptional distinguishing number.  The RTO, or traffic controlling power, will be responsible  for this. We will record all principal data, as well as the sum  he has paid ahead of time for the TOLL assortment, as per  this number. At the cost assortment office, a peruser will be  decisively situated. The assessment sum will be taken from  the vehicle's prepaid equilibrium at whatever point it goes  through a tollgate. Another balance will be set up. On the off  chance that one's equilibrium is insufficient, his refreshed  equilibrium will be negative. To resolve this issue, we have  a camera out and about that catches the image of the  significant vehicle. Since vehicles are not expected to stand  by, gridlock at cost squares is limited, and fuel utilization is  brought down. This is a critical advantage of this framework.
Keywords: Toll Collection; RFID; GSM; FASTag; Electronic Toll system